PENGEMBANGAN DIGITAL GAME BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN PENYUSUNAN KARYA INOVATIF BAGI GURU SD GUGUS SRIKANDI - Dewi Nilam Tyas; Farid Ahmadi; Sri Sulistyorini; Galih Mahardika C. Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract Some of the problems experienced by the Gugus Srikandi teachers encourage the development of Digital Game Based Learning to improve the Skills of Composing Innovative Works for Elementary School teachers of Gugus Srikandi, given the lack of skills in composing innovative works based on digital games. The selected digital game platforms are Kahoot, Quizizz and Educand considering that these platforms are easy to operate but effective for the student learning process and can train teachers to develop innovative writing skills. The activities are carried out in a combination of offline and online with the following methods: 1) pretest 2) presentation of material on the preparation of innovative works, 3) exposure to various types of and types of digital games, tutorials on compiling digital game based learning using the Kahoot, Quizizz and Educandy applications, 4) Assistance in the preparation of innovative digital game based learning works by the service team, representatives from teachers will present the results, 5) post-test. The conclusion of this activity are an increase in understanding of the principles of innovative learning by utilizing Digital Game Based Learning, teachers provide positive responses and are able to apply the understanding that has been obtained through this activity as well as increasing skills. the preparation of innovative works through Digital Game Based Learning using the Kahoot, Quizizz and Educandy platforms as innovative learning media. Abstrak Beberapa permasalahan yang dialami guru-guru Gugus Srikandi mendorong kegiatan pengabdian Pengembangan Digital Game Based Learning untuk Meningkatkan Keterampilan Penyusunan Karya Inovatif bagi Guru SD Gugus Srikandi mengingat kurangnya keterampilan penyusunan karya inovatif berbasis digital game. Platform digital game yang dipilih adalah Kahoot, Quizizz dan Educand mengingat platform ini mudah dioperasikan namun efektif bagi proses pembelajaran siswa serta dapat melatih guru mengembangkan keterampilan penyusunan karya inovatif. Kegiatan dilakukan secara kombinasi luring dan daring dengan metode berikut: 1) pretest 2) pemaparan materi mengenai penyusunan karya inovatif, 3) paparan macam dan jenis digital game, tutorial menyusun digital game based learning menggunakan aplikasi Kahoot, Quizizz dan Educandy, 4) Pendampingan penyusunan karya inovatif digital game based learning oleh tim pengabdi, perwakilan dari guru akan melakukan presentasi hasil, 5) post-test. Kesimpulan dari kegiatan ini adalah terjadi peningkatan pemahaman mengenai prinsip pembelajaran inovatif dengan memanfaatkan Digital Game Based Learing,, guru-guru memberikan respon positif dan mampu mengaplikasikan pemahaman yang telah diperoleh melalui kegiatan ini serta meningkatnya keterampilan penyusunan karya inovatif melalui Digital Game Based Learning menggunakan platform Kahoot, Quizizz dan Educandy sebagai media pembelajaran inovatif.